PERSPEKTIF ISLAM TENTANG KONSEP LIFE SKILLS EDUCATION - Muhammad Syauqi Mubarok; Muhammad Taufik; Muhammad Ridwan Fauzi; Uus Ruswandi (Edukasi Islami: Jurnal Pendidikan Islam, 2015)
Not only in the conversation or just as a discourse that never surfaced, in the practical level and the empirical reality clearly detectable, that among the challenges of globalization which can become problematic is the imposition of trade or free market competition which means that micro madrasah graduates / school and college Islam the job is getting tougher and consequently feared unemployment madrasah graduates / school and college Islam is increasing. Therefore, Islamic colleges specifically required to produce graduates who are able to become leading competitors in the world of business and economic activities. Specifically associated with the era of globalization and free market era that gave rise to the world economic blocs such as MEA (Asean Economic Community) or AFTA (the ASEAN Free Trade Area), APEC (Asian Pacific Economic Cooperation), EAEC (East Asian Economic Caucus), Lafta (Latin American Free Trade Association), CACM (Control American Common Market), Laia (Latin American Integration Association), NAFTA (North American Free Trade), SEM (Single European Market), EFTA (European Free Trade Area) and others as well also gave rise to groups of newly industrialized countries other than the United States, Europe and Japan as South Korea, Taiwan, Hong Kong, Singapore, Thailand, Malaysia, China and other countriesÂ Kata kunci: life skills, kecakapan dasar dan instrumental, soft skills, life skills education, perspektif Islam tentang life skills education